NUTRITIONAL STATUS OF CHILDREN UNDER FIVE YEARS AGE IN RURAL AREAS OF MARDAN - Khan, Noor Ahmed; Shah, Muhammad Zahir; Alf, Nina (Journal of Ayub Medical College Abbottabad, 1989)
ABSTRACT To assess the nutritional status of children under five years' age, a study was conducted during December 1988 in the four randomly selected villages of the target area of Pak-German IRDP, Mardan. A total of 351 children were examined for their weight and height to determine their nutritional status. WHO-NCHS reference scale was used for comparisons. As per WHO-NCHS reference 'scale 63.8% children were in >90% Wt/Ht, 21.9% in 85-90% Wt/Ht, 11.1% in 80-84% Wt/Ht and only 3.2% of the studied children were below 80% Wt/Ht scale of WHO-NCHS. The study reveals that no widespread malnutrition exists in the four villages.